The Quest of Rationality: Standardization in the Delivery of Care (Journal of Organizational Psychology, 2020)
The phenomenon of over-rationality is treated in this article from the perspective of the excessive standardization that can be observed in the management of patient care. In this case, standardization can be applied to execution work by setting operating procedures and rules that allow an action to be taken in a reproducible manner, to the definition of good practices (what Anglo-Saxons call “evidence-based medicine”), and to the introduction of performance standards. A careful analysis of the organization of patient care shows that it is conceived as an alternation of standardization and adaptation when unpredictable or specific work situations require it. As a result, over-rationality is understood as excessive standardization that may prevent usage of adaptation register. We illustrate this phenomenon of over-rationality through the application of standard operating procedures and the use of information technology. We then identify the reasons for this excess and propose in response to assert the recognition of an autonomous actor capable of judging the relevant recourse to the register of standardization and the modalities of its application
Keywords: Organizational Psychology; rationality, care pathway, information technology, standardization, personalization